The Impact of Agricultural Product Quality Upgrades on Regional Brand Performance in the Greater Bay Area - Zhang, Gongliang; He, Haoen; Lu, Weitan (Journal of Global Economy, Business and Finance, 2025)
This study explores how agricultural product quality influences the success of regional brands in the Greater Bay Area (GBA). Using game theory, it examines the interactions between government regulators, businesses, and consumers. The findings suggest that when authorities enforce strict quality standards, businesses are more likely to enhance product quality, which strengthens consumer trust and ultimately boosts brand performance. On the other hand, weak regulatory oversight may lead companies to cut corners, resulting in declining consumer confidence and a weaker market presence. By combining theoretical analysis with real-world implications, this research provides valuable insights into the role of quality improvements in strengthening regional brand competitiveness.